5.4: An active approach of TFT matrix controlling for liquid crystal cladding based beam steering device. (24th February 2021) - Liu, Hongjun; Lou, Fei; Qiu, Chengfeng
Abstract : Currently, Light Detection and Ranging (LiDAR) system has been widely used in various applications. However, the commercialized solution can hardly meet the rising demands, especially in autonomous driving vehicles. To further improve the laser scanning rate, life‐time and possibly lowering the cost, the main technology trend is through replacing the mechanical rotational parts with solid structures. Among those new emerging technology approaches, liquid‐crystal‐based beam steering device is one of the promising routes. In this work, for the first time in reports, the physics of such liquid‐crystal‐based devices are thoroughly explained through numerical simulation and modeling. In addition, a new device architecture with thin film transistors (TFTs) matrix and its driving methods are also introduced. With the improved driving electrodes (using TFTs panel), a wide beam steering angle (±42°) can be achieved. Meanwhile, the device remains as a reprogrammable piece even after fabrication, leaving enough room for further upgrades in terms of driving algorithm.